Redesigning Face-to-face into Online Learning for Speaking Competence during COVID-19: ESP for Higher Education in Indonesia - Kusumawati, Anggara Jatu (Universitas Negeri Makassar, 2020)
During the time of COVID-19, students should study at home and class is conducted fully online. However, classes in higher education are mostly planned for Face-to-Face (F2F) learning. To deal with the situation, educators seek an alternative learning design to be implemented and it is expected to have either comparable or improved learning outcome. This study describes Online Learning (OL) design which assesses speaking performance in ESP classes. The participants of the study were students year 2019 (N=118) and students year 2020 (N=96) joining English for Electrical Engineering (EEE) which has the same syllabus and learning goal. A proposed Gagne’s Nine Events of Instruction is analyzed, planned, implemented, and assessed its effectiveness of speaking activities which were done in the former-year-class (using F2F method) then applied in current class (using OL method). The result of F2F and Online Learning (OL) outcome were compared. To complete the analysis, a sequence of questionnaire was given to the students. The results indicates that using Gagne’s Nine Events of Instruction, speaking activity in online learning classroom, achieved satisfactory result. Designing OL both synchronous and asynchronous method for speaking is as effective as F2F. This study may open another research prospect on barriers in OL, how to assess speaking performance via online platform, or others.